Use Of The Ward And Peppard Method In Planning Strategic System Information: Systematic Literature Review - Muhamad Rizky (International Journal of Industrial Innovation and Mechanical Engineering, 2024)
Strategic planning of information systems needs to be used, because it can support business strategies in organizations or companies in order to achieve business goals more quickly. One method that can be used in strategic planning of information systems is the Ward and Peppard method. This method has a clear framework and also has analysis techniques that focus on business needs & information technology for the future. The purpose of this study is to see the use of the Ward and Peppard method in strategic planning of information systems. The method used in this study is a literature study. The results of this study are that the Ward and Peppard method in strategic planning of information systems can be used as one of the preferred methods that can be used in carrying out strategic planning of information systems in various sectors of life.